Wideband multi port reflectometer in microstrip planar technology for microwave imaging application - Che Yob, Rashidah (2012)
This article presents a wideband multi-port reflectometer formed by three-section coupled-line coupler and two-stage Wilkinson power divider. The analysis is done through calculation using the simple mathematical equations and the simulation results of three-section coupled-line coupler, two-stage Wilkinson power divider and wideband multi-port reflectometer via the use of Agilent's Advance Design Systems (ADS) software. The wideband multi-port reflectometer has demonstrated good performance for the frequency range of 1 to 6 GHz.